Exploring The Dynamics Of Ethnic Entrepreneurship In North Sulawesi: A Descriptive Study On Javanese Ethnic Entrepreneurs - Mandagi, Deske W.; Nikolas Fajar Wuryaningrat; Steven Tumbelaka; Abraham Lalengboto (SEAN Institute, 2024)
This study centers around the intricate interplay between Javanese ethnic entrepreneurs and the economic landscape of North Sulawesi, aiming to elucidate the factors that drive these entrepreneurs to establish businesses in a region marked by distinct cultural, linguistic, and customary differences. While existing research has explored the economic contributions of ethnic entrepreneurs, few have ventured into contexts where cultural dissonance is pronounced. Conducting a comprehensive descriptive analysis involving 385 respondents, this research sheds light on the motivations and dynamics behind the choices made by Javanese entrepreneurs to engage in business activities within the diverse socio-cultural milieu of North Sulawesi. The findings reveal a vibrant and dynamic business ecosystem in the region, fostering a symbiotic relationship between the entrepreneurial endeavors of the Javanese ethnic community and the broader economic development of North Sulawesi. By uncovering the mechanisms that underpin the success of Javanese ethnic entrepreneurs in a culturally disparate environment, this study contributes to a nuanced understanding of how economic support from within ethnic communities can drive regional growth. The results imply the existence of a mutually beneficial relationship wherein the adaptability and resilience of Javanese entrepreneurs converge with the open and dynamic business ecosystem of North Sulawesi, ultimately facilitating economic progress for both the ethnic group and the broader region.